Development of Learning Media As a Supporter Online Learning in Computer Network Courses - Army Trilidia Devega (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
The results of this study are as follows: (1) The validity of interactive learning media is declared valid in terms of content with a value of 0.85, (2) the practicality of interactive learning media is obtained from the teacher's response and student responses, from the student's response it is obtained an average of 87, 33 and the teacher's response was 93.57 with the practical category. (3) the effectiveness of interactive learning media obtained from student learning scores after using learning media obtained the number of students who passed were 26 students (86.7%) of 30 students and stated that the media was effective for improving student learning outcomes through the Gain score test with a value of 0 ,53 medium category. Keywords: Interactive learning media, online learningDOI: http://dx.doi.org/10.23960/jpvti.v3.i2.202106